YOUTH SOCIAL ACTIVITY IN CIVIL SOCIETY GROWTH AND DEVELOPMENT FACTOR - Azam Abdievich Abdullaev (Journals Park Publishing, 2022)
This article discusses the social activity of young people, their role and place in civil society. The role of democratic reforms in the socio-political life of the country in recent years. Political and legal culture of youth in the development of civil society. From a scientific point of view, the social participation of youth in public policy reforms.
Keywords: social activity, civil society, rule of law, democratic reforms, political, legal culture of youth, democratic processes